Kedudukan Hukum Saksi Instrumentair Terkait Keautentikan Akta Notaris - Anggelina, Ni Putu (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 3 No 3 (2018)DO - 10.24843/AC.2018.v03.i03.p10, 2019)
The legal status of a Notary employee in his capacity is a witness of the Instrumentair to support the validity of an authentic deed which is inseparable and has legal consequences for the deed of the Notary. Notary deed that raises the law causes the Notary employee to work as a witness instrument in the deed to be the party responsible and responsible for the law that appears. The legal issue in this journal is the Responsibility for the accountability of instruments in the deed of a Notary? And how to place the legal position in the instrumentation in terms of supporting the Notary deed related to the Notary's responsibility to keep the confidentiality of the deed which is made by him based on Article 16 Paragraph (1) Letter F and Article 40 of the UUJN Amendment?, This article is analyzed by normative legal research methods with a study of Article 16 paragraph (1) letter f UUJN Changes that still involve obscurity of legal norms. The purpose of this study is to examine the accountability of the instrumentair in the deed of the Notary and also provide understanding in terms of the legal position of the instrumentair selection related to the authenticity of the Notary deed. The results of the study through the journal can prove the lawsuits related to the substance of the deed whose signing involved him, remembering his capacity only employees who are functioned by a Notary to prepare the deed. The legal position of viewing related to the occupation of the Notary keeps the confidentiality of the deed whose production is made based on Article 16 paragraph (1) letter f and Article 40 of the UUJN. Therefore the instrumentair witness cannot apply Article 322 of the Criminal Code because his capacity as an election is not bound by professional ownership. Witness instructors who do not support the confidentiality of Notary documents. Status hukum pegawai Notaris dalam kapasitasnya menjadi saksi Instrumentair guna mendukung sahnya suatu akta autentik merupakan hal yang tak terpisahkan dan memiliki konsekwensi hukum terhadap akta Notaris. Akta Notaris yang menimbulkan persoalan hukum menyebabkan pegawai Notaris yang berfungsi sebagai saksi instrumentair dalam akta menjadi pihak yang dianggap tahu dan bertanggung jawab atas persoalan hukum yang muncul. Isu hukum dalam jurnal ini adalah Bagaimanakah tanggungjawab saksi instrumentair dalam akta Notaris? Dan bagaimanakah kedudukan hukum saksi instrumentair dalam hal mendukung keautentikan akta Notaris terkait adanya kewajiban Notaris menyimpan kerahasiaan akta yang pembuatannya dilakukan olehnya berdasarkan Pasal 16 Ayat (1) Huruf F dan Pasal 40 UUJN Perubahan ?, Artikel ini dianalisis dengan metode penelitian hukum normatif dengan kajian terhadap Pasal 16 ayat (1) huruf f UUJN Perubahan yang masih terdapat kekaburan norma hukum. Tujuan penelitian ini adalah mengkaji secara mendalam tanggungjawab saksi instrumentair dalam akta Notaris serta memberikan pemahaman dalam hal kedudukan hukum saksi instrumentair terkait dengan keautentikan akta Notaris. Hasil kajian melaui jurnal ini diketahui bahwa saksi instrumentair tidak bisa dituntut secara hukum terkait substansi akta yang penandatanganannya melibatkan dirinya, megingat kapasitasnya hanya pegawai yang difungsikan oleh Notaris untuk mempersiapkan akta. Kedudukan hukum saksi instrumentair terkait adanya kewajiban Notaris menyimpan kerahasiaan akta yang pembuatannya dilakukan olehnya berdasarkan Pasal 16 ayat (1) huruf f dan Pasal 40 UUJN Perubahan tidak diwajibkan secara pasti harus menjaga kerahasiaan subtansi akta. Oleh sebab itu terhadap saksi instrumentair tidak bisa diterapkan Pasal 322 KUHP karena kapasitasnya sebagai saksi tidak melekat jabatan profesi. Saksi instrumentair yang tidak menjaga kerahasiaan dokumen Notaris perbuatannya diklasifikasikan perbuatan melawan hukum.